Relation between ST segment elevation during dobutamine stress test and myocardial viability after a recent myocardial infarction. - Elhendy, A. (1997)
OBJECTIVE: To assess the relation between ST segment elevation during the dobutamine stress test and late improvement of function after acute Q wave myocardial infarction. PATIENTS AND DESIGN: 70 patients were studied a mean (SD) 8 (3) days after acute myocardial infarction with high dose dobutamine-atropine stress echocardiography and a follow up echocardiogram at 85 (10) days. A score model based on 16 segments and four grades was used to assess left ventricular function. Functional improvement was defined as a reduction of wall motion score > or = 1 in > or = 1 segments at follow up. INTERVENTION: Myocardial revascularisation was performed in 23 patients (33%) before follow up studies. RESULTS: ST segment elevation occurred in 40 patients (57%). Late functional improvement occurred in 35 patients (50%). Functional improvement was more common in patients with ST segment elevation (68% v 30%, P < 0.005) and they had a higher mean (SD) number of improved segments at follow up (1.9 (2.2) v 0.5 (1.1), P < 0.005). The wall motion score index decreased between baseline and follow up in patients with ST segment elevation (1.54 (0.50) v 1.48 (0.43), P < 0.05) but not in patients without ST segment elevation (1.39 (0.60) v 1.45 (0.47)). The accuracy of ST segment elevation for the prediction of functional improvement was similar to that of low dose dobutamine echocardiography in patients with anterior infarction (80% v 83%) and in patients who underwent revascularisation (78% v 83% respectively). CONCLUSION: In patients with a recent Q wave myocardial infarction, dobutamine-induced ST segment elevation is a valuable marker of myocardial viability particularly when the test is performed without or with suboptimal echocardiographic imaging.